Treatment tactics in patient with articular pathology and concominant disorders of upper gastrointestinal tract - O N Minushkin (Научно-практическая ревматология)
Objective. To study nise efficacy and safety in pts with rheumatic diseases (RD) with concomitant disorders of upper gastrointestinal tract (GIT). Material and methods. An open uncontrolled multicenter nise study was conducted on 600 pts (mean age 54,8 years) with RD (rheumatoid arthritis - RA, osteoarthritis - OA, spine osteochondrosis with radicular syndrome - ОС). 20% of pts had G1 diseases at inclusion. Nise® was administered 200 mg/day for 30 days. An additional examination (esophagogastroduodenoscopy - EGDS, US, laboratory investigation) was performed in 30 pts with RD (20 - OA, 10 - ОС, mean age 48,4 years) and concomitant GI disorders (gastric ulcer in remission, erosive duodenitis, chronic pancreatitis, cholecystilis). Results. Nise® was effective in 40% from 600 pts with RD. (% of pts had non severe GI adverse events. The drug was withdrawn due to dyspepsia in only 0,2% of cases. Pain syndrome was eliminated in 90% from 30 pts with RD and GI disorders. 25 from them completed the trial. Severe adverse events did not appear. EGDS did not revealed exacerbation or appearance of new GI ulcers. Conclusion. Nise® is an effective and relatively safe NSAID which can be administered in pts with RD and concomitant GI disorders with EGDS control.